2020
DOI: 10.3390/pathogens9040252
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes as Targets for Adjuvants

Abstract: Inflammasomes are an essential part of the innate immune system. They are necessary for the development of a healthy immune response against infectious diseases. Inflammasome activation leads to the secretion of pro-inflammatory cytokines such as IL-1β and IL-18, which stimulate the adaptive immune system. Inflammasomes activators can be used as adjuvants to provide and maintain the strength of the immune response. This review is focused on the mechanisms of action and the effects of adjuvants on inflammasomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 129 publications
(145 reference statements)
1
22
0
Order By: Relevance
“…Experiments utilizing analogs of dsRNA (poly-I:C) and ssRNA (ssRNA40) demonstrated that an NLRP3mediated response could be activated by 'virus mimetic' RNA species (Allen et al 2009). Whereas the NLRP3 inflammasome is an essential component in host defense against infection through sensing of viral RNA (Ivanov et al 2020), its overshooting activity can be highly destructive. An excessive inflammatory response results in the progression of ARDS, with the NLRP3 inflammasome as key player.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments utilizing analogs of dsRNA (poly-I:C) and ssRNA (ssRNA40) demonstrated that an NLRP3mediated response could be activated by 'virus mimetic' RNA species (Allen et al 2009). Whereas the NLRP3 inflammasome is an essential component in host defense against infection through sensing of viral RNA (Ivanov et al 2020), its overshooting activity can be highly destructive. An excessive inflammatory response results in the progression of ARDS, with the NLRP3 inflammasome as key player.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes are an essential part of the innate immune system and their activation can stimulate the adaptive immune system; thus, they are often the targets for vaccine adjuvants [ 84 ]. The role of QS-21 in activating NOD-like receptor protein 3 (NLRP3) inflammasome seems to be complicated.…”
Section: Mechanism Studies Of Qs-21mentioning
confidence: 99%
“…As a whole, the ability of ASC specks to aggregate cytosolic proteins, to be released into the extracellular space, to localize in subcapsular niche of lymph nodes and to have controlled degradation when phagocytized gives specks the potential to contribute to antigen presentation during an infection or even in vaccination. Moreover, alum adjuvants used in human vaccines have their activity linked to the activation of ASC specks producing NLRP3 inflammasome [29][30][31].…”
Section: Physiological Roles Of Easc Asc Specks In Adaptive Immune Responsementioning
confidence: 99%
“…Thus, ASC specks present important roles in adaptive immunity independently of inflammasome activation, related to antigen uptake and presentation and polarization of immune response [31,33].…”
Section: Physiological Roles Of Easc Asc Specks In Adaptive Immune Responsementioning
confidence: 99%